Constitutional Protections of Press and Media Freedoms in Jordan and Indonesia Amid Challenges from Artificial Intelligence and International Legal Frameworks - AlOmran, Nayel; Rebhi, Tourkia (Universitas Negeri Semarang, 2025)
The Jordanian Constitution’s protection of press and media freedom faces significant challenges due to the growing body of legislation that criminalizes and punishes media related activities. With increasing regulations restricting freedom of expression, the question arises whether the constitutional framework in Jordan effectively safeguards press freedoms despite these constraints. The situation is further complicated by the influence of international law, which shapes media regulations globally, and a comparison with Indonesia’s legal approach highlights the similarities and differences in how both countries address media freedom and state control. In this context, the impact of artificial intelligence on journalistic integrity and media bias has become a crucial factor. AI technologies are increasingly being employed in Jordan to monitor, filter, and regulate media content, potentially influencing editorial independence and contributing to biased reporting, which raises significant concerns about the ethical use of AI in media regulation. The analysis reveals that while constitutional provisions theoretically protect press and media freedoms, the enactment of various laws, media regulations, and ministerial decisions often contradict these protections, placing significant control in the hands of the ruling authority. This situation is exacerbated by heavy penalties, including imprisonment and exorbitant fines, which restrict the ability of journalists and media outlets to operate freely. Also, some amendments to media laws seem to violate constitutional principles, posing a direct threat to the balance between state authority and media autonomy. In this study, the most important result that have been achieved: Freedom of the press and media is intrinsically linked to a broad range of civil and political rights, and it cannot be discussed in isolation. The protection of this freedom requires strong constitutional guarantees that align with both national laws and international standards. Legal protections must be in place to prevent unjustified restrictions that could limit press and media freedom.